1978
DOI: 10.1159/000280177
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Water Cystometry and CO<sub>2</sub> Cystometry

Abstract: Comparison of the results obtained with medium-fill water cystometry and rapid-fill CO2 cystometry were done in 102 consecutive patients. In 99 patients the cystometric diagnoses were identical. In 3 patients we found detrusor hyperreflexia with water but a normal cystometrogram with CO2. We concluded that CO2 cystometry gives as valid information as water cystometry. Volume at first desire to void, bladder capacity and bladder compliance is approximately 50% higher in water cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1979
1979
2007
2007

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…As the filling medium we adopted carbon dioxide, which is unphysiological and gives no information on voiding. Nordling et al [1978] described a comparative study of water cystometry and carbon dioxide cystometry. They concluded that carbon dioxide cystometry gives information as valid as that of water cystometry.…”
Section: Discussionmentioning
confidence: 99%
“…As the filling medium we adopted carbon dioxide, which is unphysiological and gives no information on voiding. Nordling et al [1978] described a comparative study of water cystometry and carbon dioxide cystometry. They concluded that carbon dioxide cystometry gives information as valid as that of water cystometry.…”
Section: Discussionmentioning
confidence: 99%
“…The discussion concerning the use of water opposed to CO2 during cystometry seems to continue still [11], We found it advantageous to use CO2 at a relatively high flow rate, since examination could thereby be terminated more quickly. Children are often impatient and this factor alone can influence the result of an examination [10].…”
Section: Discussionmentioning
confidence: 94%
“…In a prospective study of 303 patients using medium fill water cystometry in the supine position (Walter, 1978), detrusor hyperreflexia was found in 15% of the patients. It has been shown that medium fill water cysto-metry and rapid fill COz cystometry have the same diagnostic specificity (Nordling et al, 1978b), so it seems unlikely that the different filling medium and filling rate are responsible for the difference. On the other hand, the technique used by Walter revealed only the type of detrusor hyperreflexia described in this paper as detrusor hyperreflexia Type 1A.…”
Section: Discussionmentioning
confidence: 99%